Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1103/physrevlett.112.047402
|View full text |Cite
|
Sign up to set email alerts
|

Infrared- and Raman-Spectroscopy Measurements of a Transition in the Crystal Structure and a Closing of the Energy Gap of BiTeI under Pressure

Abstract: BiTeI is a giant Rashba spin splitting system, in which a noncentrosymmetric topological phase has recently been suggested to appear under high pressure. We investigated the optical properties of this compound, reflectivity and transmission, under pressures up to 15 GPa. The gap feature in the optical conductivity vanishes above p ∼ 9 GPa and does not reappear up to at least 15 GPa. The plasma edge, associated with intrinsically doped charge carriers, is smeared out through a phase transition at 9 GPa. Using h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
78
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 24 publications
8
78
0
Order By: Relevance
“…It can be observed that the initial rhombohedral structure is stable up to 7 GPa, where a first-order phase transition can be unambiguously identified by the appearance of new Bragg peaks and the disappearance of other features. The phase transition pressure is similar to that reported for BiTeI [14][15][16]18]. The onset of the phase transition is placed at 7 GPa but the initial and high-pressure phases coexist up to at least 12 GPa.…”
Section: B Xrd Measurements In Compressed Bitebrsupporting
confidence: 83%
See 2 more Smart Citations
“…It can be observed that the initial rhombohedral structure is stable up to 7 GPa, where a first-order phase transition can be unambiguously identified by the appearance of new Bragg peaks and the disappearance of other features. The phase transition pressure is similar to that reported for BiTeI [14][15][16]18]. The onset of the phase transition is placed at 7 GPa but the initial and high-pressure phases coexist up to at least 12 GPa.…”
Section: B Xrd Measurements In Compressed Bitebrsupporting
confidence: 83%
“…This makes a difference in relation to the discussed observation of the pressure-induced TQPT in BiTeI [13,14,16,18]. In this respect, the closure of the band gap is likely to occur in BiTeI above 3.0 GPa, while in BiTeBr it should not occur below 6 GPa; i.e., very close to the pressure for the transition to the high-pressure phase.…”
Section: Transport Measurements Under Pressurementioning
confidence: 89%
See 1 more Smart Citation
“…The transition is accompanied by the band-gap closing and re-opening, and the band inversion between the bands mentioned above occurs at higher pressures. Since the publication of Bahramy et al, the X-ray diffraction, the spectroscopy, and the band calculation were performed on BiTeI to investigate the topological phase transition [6][7][8]. These experiments suggested that a minimum ratio of lattice constants, c/a, makes a significant contribution to the topological transition; the free-carrier spectral weight shows a maximum and the band-gap closes when the c/a has a minimum.…”
Section: Introductionmentioning
confidence: 99%
“…In experiments of x-ray powder diffraction and infrared spectroscopy, the lattice parameter ratio c/a shows a minimum between 2.0 and 2.9 GPa and the infrared spectra reveal a maximum in optical spectral weight of the charge carriers [29], though there was no clear evidence in the other infrared study under pressure [30]. Another report on an x-ray diffraction experiment estimated a topological transition point near 4.5 GPa [31].…”
mentioning
confidence: 95%